Identifying candidate items for a health-related quality of life measure in young children with respiratory illness: A scoping review of generic and disease-specific measures - Michaile Gizelle Anthony; Graeme Hoddinott; Dzunisani Patience Baloyi; Anneke Catharina Hesseling; Marieke Margreet van der Zalm (PLoS ONE, 2025)
Background Health-related quality of life (HRQoL) in young children affected by respiratory illnesses remains understudied, particularly in low- and middle-income countries (LMICs), where the burden of these diseases is disproportionately high. Existing HRQoL measures, including both generic and respiratory disease-specific measures, have been reviewed to identify key components that can guide the development of a novel HRQoL tool for young children (0–5-years) with respiratory illnesses. The study aimed to identify candidate items from existing HRQoL measures to inform the development of a new HRQoL tool for young children (0–5 years-old) with respiratory illnesses in a LMIC setting. Methods A scoping review was conducted using PubMed, EBSCOhost, and PsycArticles databases Keywords included variations of the following terms ‘quality of life’, ‘health-related quality of life’, ‘wellbeing’, ‘questionnaire’, ‘instrument’, ‘measure’, ‘children’, ‘toddler’, ‘paediatric’, ‘child*’, ‘develop’ or ‘validation’. The search was limited to English-language articles published between January 2000 and November 2023. Deductive thematic analysis was used to organise the measures and synthesise cross-cutting components. Results Out of 1823 articles, data were extracted from 72 articles reporting on 41 measures. Of these, 20 were generic, and 21 were specific to respiratory diseases. The measures’ key dimensions included physical and emotional health, social support, and school functioning. However, few measures, targeted children 0–5-years, and none incorporated child-specific methods for assessing HRQoL. Existing tools varied widely in their domains and definitions, often lacking consistency and not adequately considering the developmental milestones. Furthermore, most tools were developed in high-income settings (HIC), with limited adaption to the socio-economic burden and disease burden contexts in LMICs. Conclusion There is an urgent need for a comprehensive HRQoL measure tailored to young children with respiratory illnesses, particularly one designed for use in LMICs. Such a tool should address developmental milestones, cultural sensitivity, and the unique socio-economic challenges faced in these settings.